New models of Parkinson’s like neuroinflammation in human microglia clone 3: Activation profiles induced by INF-γ plus high glucose and mitochondrial inhibitors - De Chirico, Francesca; Poeta, Eleonora; Babini, Giorgia; Piccolino, Iliana; Monti, Barbara; Massenzio, Francesca (Frontiers in Cellular Neuroscience, 2022)
Microglia activation and neuroinflammation have been extensively studied in murine models of neurodegenerative diseases; however, to overcome the genetic differences between species, a human cell model of microglia able to recapitulate the activation profiles described in patients is needed. Here we developed human models of Parkinson’s like neuroinflammation by using the human microglia clone 3 (HMC3) cells, whose activation profile in response to classic inflammatory stimuli has been controversial and reported only at mRNA levels so far. In fact, we showed the increased expression of the M1 markers iNOS, Caspase 1, IL-1β, as well as the M2 marker TREM2 in response to IFN-γ plus high glucose, a non-specific disease stimulus that emphasized the dynamic polarization and the heterogenicity of the microglial population. More specifically, we demonstrated the M1 polarization of HMC3 cells through the upregulation of iNOS expression and nitrite production in response to the Parkinson’s like stimuli, 6-hydroxidopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), the latter depending on the NF-κB pathway. Furthermore, we identified inflammatory mediators that promote the pro-inflammatory activation of human microglia as function of different pathways that can simulate the phenotypic transition according to the stage of the pathology. In conclusion, we established and characterized different systems of human microglia clone 3 (HMC3) cells activation as in vitro models of Parkinson’s like neuroinflammation.